Japanization what the world can learn from Japan's lost decades - Pesek, William (Bloomberg Press, an imprint of Wiley, 2014)
An in-depth look at Japan's economic malaise and the steps it must take to compete globally. In Japanization, Bloomberg columnist William Pesek-based in Tokyo-presents a detailed look at Japan's continuing twenty-year economic slow-down, the political and economic reasons behind it, and the policies it could and should undertake to return to growth and influence. Despite new Prime Minister Shinzo Abe's promise of economic revitalization, investor optimism about the future, and plenty of potential, Japanization reveals why things are unlikely to change any time soon.